Bone marrow mesenchymal stem cells differentiate into intestinal epithelioid cells through the ERK1/2 pathway - Jiang, Ting; Shi, Meng-lin; Xia, Geng; Yang, Yi-Na; Xu, Jia-Min; Lei, Yun-Jie; Tang, Ying-Mei; Yang, Jin-Hui (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Previous studies have found that the injection of rat bone marrow mesenchymal stem cells (rBMSCs) in a mouse model of acute hepatic failure can significantly relieve intestinal damage and endotoxemia. However, the mechanism of this process remains unknown. This study demonstrated the differentiation of rBMSCs into enterocyte-like cells and possible molecular mechanism with the aim of finding new treatment for intestinal epithelial injury and endotoxemia in liver failure.Materials and Methods: rBMSCs were isolated from femurs and tibias. Differentiation was induced by co culturing (rBMSCs+mIEC-6) using Transwell; after three, seven and ten days of induction, specific expression molecules were examined. To inhibit the activities of ERK1/2 signalling pathway, the inhibitor of MEK1/2, U0126 was added into the co-cultured medium. After 36 and 72 hours of inhibition, western blot analysis was used to evaluate the expression of specific molecules, including the specific markers of ERK1/2 signalling pathway (p-MEK1/2 and p-ERK1/2).Results: The rBMSCs can differentiate into enterocyte-like cells as co-cultured with mIEC-6. U0126 could temporarily inhibit the activity of MEK1/2, but MEK increased after 72 hours, and the epithelioid differentiation of rBMSCs was consistent with the change of MEK. Conclusion: rBMSCs can differentiate into intestinal epithelium by co culturing with mIEC-6, and the ERK1/2 signalling pathway can be involved in regulating the differentiation of rBMSCs. However, further research is still needed to perfect the network of mechanisms.